Analysis of Contractor's Knowledge Level about Construction Safety Management System Budget Plan Components (Case Study: Construction Project in Padang City) - Prima Zola; Viola Paramita Susanti; M. Giatman; Annisa Prita Melinda; Fitra Rifwan (invotek, 2022)
Work accident prevention is cheaper than responding responsively after an accident. Common problems are weakness and a lack of predicted levels of risk for a job that could potentially be a work accident. Risk Control is undoubtedly something that must be designed before the work is done. This control must be supported by costs to run a Construction Safety Management System (SMKK). The initial observations and references that have been conducted and collected indicate the problem that the financing does not appear in the Budget Plan of the contractors in several construction projects when participating in the tender auction at the research site, namely: The City of Padang. There are limitations of information media, socialization, and implementation instructions become challenges in running it. This fundamental problem gave rise to an idea to carry out research. This research has been conducted to explore the problem of the level of knowledge of contractors about the financing of smkk. The data in this study was obtained by survey, in detail, disseminating questionnaires online to samples, namely: contractors in the city of Padang. The questionnaire has been analyzed, resulted the level of knowledge of this contractor is quite good in the level of knowledge about the components of the budget plan of SMKK. There is no problem with the contractor's knowledge related to the budget plan, except: readiness and planning for the system of budget.